2011
DOI: 10.1002/htj.20383
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on the use of nanofluids in natural convection heat exchangers using a mixture‐phase approach

Abstract: In the present research, the behavior of a Newtonian nanofluid (water-Al 2 O 3 ) in a mixture phase model approach is numerically examined. The process of heating is done in two different ways. Deterioration was found in the mean Nusselt number of a nanofluid in the mixture-phase model approach when compared to the mean Nusselt number of pure water. However, in the single-phase model there was an increase in the Nusselt number when compared to the Nusselt number of pure water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A comprehensive study on nanofluid heat transfer characteristics and their applications can be found in Chitra and Sendhilnathan [1], Godson and colleagues [2], and Sarkar [3]. Many investigations [4][5][6][7] explained that nanofluids clearly exhibit enhanced thermal conductivity, which augments with an increase in the volumetric fraction of nanoparticles. Hwang and colleagues [8] from their research observed that heat transfer coefficient of a nanofluid decreases with an increase in the size of nanoparticles, in a natural convection case in a rectangular cavity using Al 2 0 3 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive study on nanofluid heat transfer characteristics and their applications can be found in Chitra and Sendhilnathan [1], Godson and colleagues [2], and Sarkar [3]. Many investigations [4][5][6][7] explained that nanofluids clearly exhibit enhanced thermal conductivity, which augments with an increase in the volumetric fraction of nanoparticles. Hwang and colleagues [8] from their research observed that heat transfer coefficient of a nanofluid decreases with an increase in the size of nanoparticles, in a natural convection case in a rectangular cavity using Al 2 0 3 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous other theoretical investigations by different researchers (Bianco et al, 2009;Ebrahimnia-Bajestan et al, 2011;Farsad et al, 2011;Fazeli et al, 2012;Haghshenas Fard et al, 2010;Kalteh et al, 2012;Kamali and Binesh, 2010;Kamyar et al, 2012;Mahmoodi and Hashemi, 2012;Manca et al, 2012;Rana and Bhargava, 2011;Rostamani et al, 2010;Singh et al, 2012;Tahery et al, 2011;Yang and Lai, 2011;Yu et al, 2011) on nanofluid convective heat transfer were carried out, but all of them did not consider the van der Walls interaction and agglomeration phenomena of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%